2012
DOI: 10.1016/j.aquaculture.2012.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Induction of settlement in larvae of the mussel Mytilus galloprovincialis using neuroactive compounds

Abstract: We investigated the effect on Mytilus galloprovincialis larval settlement, as well as the toxicity, of serial concentrations in filtered seawater of acetylcholine (AC), γ-aminobutiric acid (GABA); 3-isobutyl-1-methylxanthine (IBMX); and the potassium ion in the form of potassium chloride (KCl) and potassium sulfate (K2SO4). All the substances assayed induced larval settlement and peak responses were above 90% in exposures to 10− 2 mol L− 1 (M) AC, 10− 4 and 10− 5 M epinephrine, 10− 3 M GABA and 20, 30 and 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Individuals that maintained firm attachment to the substratum were considered settled, and those moving freely with no resistance were considered unsettled. This technique provides a reliable and larvae and is well-established in the literature (Ganesan et al 2010(Ganesan et al , 2012Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012;Wilkens et al 2012;McDonald et al 2014). Furthermore, we have found 205 this method to be consistently more reliable than other methods (e.g.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Individuals that maintained firm attachment to the substratum were considered settled, and those moving freely with no resistance were considered unsettled. This technique provides a reliable and larvae and is well-established in the literature (Ganesan et al 2010(Ganesan et al , 2012Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012;Wilkens et al 2012;McDonald et al 2014). Furthermore, we have found 205 this method to be consistently more reliable than other methods (e.g.…”
mentioning
confidence: 60%
“…Stock solutions (10× concentrates) of each treatment level were prepared by dissolving compounds in 0.45 μm filtered seawater (FSW) 160 immediately prior to settlement assays. These concentrations were chosen based on a pilot study and our experience with other mussel species (Alfaro et al 2011;Sánchez-Lazo et al 2012). .…”
mentioning
confidence: 99%
“…It is unclear whether this effect was caused by a coupling of the metamorphic gene regulatory network to the induced pre-metamorphic behavior/process prior to the event, or whether acetylcholine is directly involved in the morphogenic signalling pathway during the event. While acetylcholine is a potent inducer of larval settlement in some bivalve species (Yu et al 2008;Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012), no effect on attachment or metamorphosis has been observed in the five Haliotis spp. tested thus far (H. discus [Fukazawa et al 2001], H. discus hannai [Akashige et al 1981], H. diversilcolor supertexta [Yu et al 2010], H. gigantea [Fukazawa et al 2001], H. rufescens [Morse et al 1979]).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this effect was caused by a coupling of the metamorphic gene regulatory network to the induced pre-metamorphic behavior/process prior to the event, or whether acetylcholine is directly involved in the 17 morphogenic signalling pathway during the event. While acetylcholine is a potent inducer of larval settlement in some bivalve species (Yu et al 2008;Alfaro et al 2011;Young et al 2011;Sánchez-Lazo et al 2012) Resembling the effects of GABA, KCl, acetylcholine and dopamine, glutamine also reduced swimming activity in H. iris larvae within the first two days of exposure. Although there was some indication of induced attachment at high concentrations (10 -4 mol L -1 ), high mortalities (ca.…”
Section: Discussionmentioning
confidence: 99%
“…실험에 이용한 신경전달물질은 serotonine (5-HT, sigma USA), gamma amino butyric acid (GABA, sigma USA), et al, 1985;Bonar et al, 1990;Coon et al 1990a,b;Walch et al, 1999;Fang et al, 2001;Kang et al, 2004;García-Lavandeira et al, 2005;Gao and Liu, 2006;Yang et al, 2008;Yang et al, 2011;Sánchez-Lazo et al, 2012;Teh et al, 2012;Mesías-Gansbiller et al, 2013;Yang et al, 2013 (Pawlik, 1990;Couper and Leise, 1996;Leise et al, 2001), 진주조개류 인 Pinctada maxima (Zhao et al, 2003), Pinctada fucata martensii (Yu et al, 2008), Pteria penguin …”
Section: 부착유인 효과mentioning
confidence: 99%